Managing Cross-Border Conflicts Through Volunteer Commitment: A Comparative Study Between Religious and Non-profit Organizations in the San Diego–Tijuana Area - Cerdá Suárez, Luis Manuel; Valero Matas, Jesús Alberto; Jaramillo Cardona, Martha Cecilia; Ramírez Ramirez, Margarita (Frontiers in Psychology, 2020)
San Diego and Tijuana configure two big cities that have faced each other across the international boundary between United States and Mexico for over 180 years. Within this context, the relationship emerging at the border can be characterized under different categories of individual, social, economic and political situations connecting each side. Additionally, in recent years the literature on cross-border conflicts has extensively focused on volunteers as informal agents helping children and other groups of population, but relatively little research has addressed the practical and managerial work and implications of the volunteers themselves. As actors of cross-border communities, volunteers play a relevant role in effective short-term migrants’ settlement, but it is also observed that the profile of volunteers in religious organizations differs from those belonging to non-profit institutions. Grounded on the theories of Planned Behavior and Reasoned Action suggesting that intentions to cooperate with non-government institutions are influenced directly by attitudinal values and indirectly by their beliefs related to social conflicts, this paper analyzes the nature of volunteer commitment in religious and non-profit organizations providing information about managerial practices for newly arrived migrants. The main purpose of this study is to investigate the relevance of volunteer commitment as an instrument for managing cross-border conflicts in the particular context of San Diego and Tijuana Area. Based on research using interview data collected from beneficiaries by volunteers, institutional representatives and documentary references, this manuscript highlights a psychological and individual-centric perspective of volunteer commitment but also it explores a collective communicative action expanding the range of relevant voices in decisions about volunteering. Moreover, this study provides new insights on how organizational and relational elements impact sustainable volunteer management, and points out the role played by attitudes towards non-government institutions such as religious and non-profit organizations demonstrating the relevance of volunteer commitment, transforming part of the positive attitude towards social problems into a significant intention to cooperation. Understanding the importance of the organization’s images in order to attract volunteers, these results show that commitment may become a key determinant of the volunteers’ identity linked to strategies devoted to organizational activities.